Optimization of Silkworm Pupae Fermentation by Response Surface Methodology and Products Taste Characteristics Study - Fangli QIN; Siyuan WANG; Yuxiao ZOU; Erna LI; Lixia MU; Qingrong LI (Shipin gongye ke-ji)
To establish an optimized silkworm pupae fermentation process and explore the taste characteristics of the fermented products, the effects of different bacterial species, inoculum amounts, fermentation temperatures, and fermentation times on the amino acid nitrogen content generated by fermented silkworm pupae were investigated. Based on single factor experiments, response surface methodology was employed to optimize the silkworm pupae fermentation process. Differences in taste-contributory substances and taste before and after fermentation were elucidated. The optimal fermentation parameters were found to be 1.0% Lactobacillus sakei inoculum, fermentation temperature of 32 ℃, and fermentation time of 10 days. Under these conditions, the amino acid nitrogen content reached 0.95±0.02 g/100 g, closely aligning with the anticipated value. Compared with those in unfermented silkworm pupae, the free amino acid, nucleotide, and organic acid contents in fermented silkworm pupae were significantly increased (P<0.05), reaching 52.19±0.11, 1.01±0.03, and 65.54±1.61 mg/g, respectively. The taste activity value (TAV) of aspartic, glutamic, guanylic, adenylic, and succinic acids, which contribute to umami taste, were all above 1. Notably, glutamic and succinic acids, which were considered to be the best contributors to umami taste in fermented silkworm pupae, exhibited TAV as high as 20.06 and 138.47, respectively. The monosodium glutamate (MSG) equivalent after silkworm pupae fermentation reached 74.44 g MSG/100 g, a 6.74-fold increase compared to the pre-fermentation level. This study demonstrates that silkworm pupae fermentation can produce umami substances that yield a desired flavor, providing new insights for the development and utilization of silkworm pupae and for the production of umami substances.